Foreign Direct Investments and domestic employment of German SMEs: The moderating effect of owner-management. - Zapkau, F B; Schwens, C; Kabst, Rüdiger (Journal of Small Business Management (JSBM).)

Linking Transaction Cost and Social Exchange Theory to Explain Strategic Alliance Performance: A Meta-Analytic Structural Equation Model. - Isidor, R; Steinmetz, Holger; Schwens, C; Kabst, Rüdiger (International Journal of Strategic Business Alliances.)

Configurations of e-HRM - An Empirical Exploration. - Strohmeier, S; Kabst, Rüdiger (Employee Relations.)

A Fuzzy Security Investment Decision Support Model for Highly Distributed Systems - Yasasin, Emrah; Rauchecker, Gerhard; Prester, Julian; Schryen, Guido (1st Workshop on Security in highly connected IT systems (SHCIS 14))

Emergency Response in Natural Disaster Management: Allocation and Scheduling of Rescue Units - Wex, Felix; Schryen, Guido; Feuerriegel, Stefan; Neumann, Dirk (European Journal of Operational Research)

Risk Reduction in Natural Disaster Management Through Information Systems: A Literature review and an IS design science research agenda - Schryen, Guido; Wex, Felix (International Journal of Information Systems for Crisis Response and Management (IJISCRAM))
Natural disasters, including earthquakes, Tsunamis, floods, hurricanes, and volcanic eruptions, have caused tremendous harm and continue to threaten millions of humans and various infrastructure capabilities each year. In their efforts to take countermeasures against the threats posed by future natural disasters, the United Nations formulated the ?Hyogo Framework for Action?, which aims at assessing and reducing risk. This framework and a global review of disaster reduction initiatives of the United Nations acknowledge the need for information systems research contributions in addressing major challenges of natural disaster management. In this paper, we provide a review of the literature with regard to how information systems research has addressed risk assessment and reduction in natural disaster management. Based on the review we identify research gaps that are centered around the need for acquiring general knowledge on how to design IS artifacts for risk assessment and reduction. In order to close these gaps in further research, we develop a research agenda that follows the IS design science paradigm.
Keywords: Natural Disaster Management; Risk Reduction; Hyogo Framework; IS Design Science; Literature review

Duality in fuzzy linear programming: A survey - Schryen, Guido; Hristova, Diana (OR -Spectrum)

Writing qualitative IS literature reviews ? Guidelines for synthesis, interpretation and guidance of research - Schryen, Guido (Communications of the AIS)

Interview with Michael Rosemann on ambidextrous business process management - Kohlborn, Thomas; Müller, Oliver; Poeppelbuss, Jens; Roeglinger, Maximilian (Business Process Management Journal)

Handbuch für offene gesellschaftliche Innovation - Raffl, Celina; Lucke, Jörn; Müller, Oliver; Zimmermann, Hans-Dieter; Vom Brocke, Jan (TOGI-Schriftenreihe)

Identifying and characterizing topics in enterprise content management: a latent semantic analysis of vendor case studies - Herbst, Andrea; Simons, Alexander; vom Brocke, Jan; Müller, Oliver; Debortoli, Stefan; Vakulenko, Svitlana (European Conference on Information Systems)

Identifying the role of information systems in achieving energy-related environmental sustainability using text mining - Reuter, Nadine; Vakulenko, Svitlana; vom Brocke, Jan; Debortoli, Stefan; Müller, Oliver (European Conference on Information Systems)

How In-memory Technology Can Create Business Value: Insights from the Hilti Case - vom Brocke, Jan; Debortoli, Stefan; Müller, Oliver; Reuter, Nadine (Communications of the Association for Information Systems)

The deep structure of organizational online networking - an actor-oriented case study - Trier, Matthias; Richter, Alexander (Information Systems Journal)

Thin Capitalization Rules and Entrepreneurial Capital Structure Decisions - Maßbaum, Alexandra; Sureth-Sloane, Caren (Business Research)

Mixed methods analysis of enterprise social networks - Trier, Matthias; Behrendt, Sebastian; Richter, Alexander (Computer Networks)

Mixed methods analysis of enterprise social networks - Behrendt, Sebastian; Richter, Alexander; Trier, Matthias (Computer Networks)

Der richtige Ansprechpartner im dynamischen Interaktionsnetzwerk - Trier, Matthias; Müller, Matthias; Bobrik, Annette (HMD Praxis der Wirtschaftsinformatik)

MEDIA ENGINEERING WITH A CONTENT HUB SYSTEM. GENERIC CONTENT TRANSFORMATION FOR MOBILE MEDIA - Herzog, Michael; Trier, Matthias (International Journal of Computing)
A primary problem in multimedia content production is the plethora of formats and the resulting multiple point-to-point transformation processes in different content formatting specifications. However, these content transformation processes can be conceptually broken down into a limited set of abstract principles. This allows a unified approach that theoretically enables the transformation of any given input channel into any desired output. Based on this principle, the present article introduces the concept of Generic Content Transformation and the related project MOCCA, which develops the corresponding software implementation of generic content transformation for a variety of input and output channels. To balance technical similarities with specific properties of different media channels, we suggest a combination of an XML-based structure (MocML) and a high level authoring environment. Generic Content Transformation further allows for novel means of accessing assets via compound search algorithms. In the second part we summarize and discuss current results and experiences in three scenarios of media production, including mobile media.
Keywords: Multimedia Authoring; Mobile Content; Cross Media Production; Content Engineering; Media Retrieval

Business Intelligence 2.0 - Behrendt, Sebastian; Richter, Alexander; Schäfer, Sebastian; Trier, Matthias (Vernetzte Organisation)

Towards a Conceptualization of Online Community Health - Wagner, David; Richter, Alexander; Trier, Matthias; Wagner, Heinz-Theo (Proceedings of the 35th International Conference on Information Systems. ICIS 2014)
Along with the increasing popularity of social media and online communities in many business settings, the notion of online community health has become a common means by which community managers judge the condition or state of their communities. It has also been introduced to the literature, yet the concept remains underspecified and fragmented. In this paper, we work toward a construct conceptualization of online community health. Through a review of extant literature and dialogue with specialists in the field, we develop a multi-dimensional construct of online community health, consisting of seven elements. In writing this paper, we attempt to foster theory development around new organizational forms by advancing a new and important construct. The paper further provides guidance to the managers of social media and online communities by taking a systematic look at the well-being of their communities.
Keywords: Social media; Online communities; Online community success; Online community health; Construct conceptualization

On Consumer Purchasing Behavior in Electronic Markets - Herrmann, Philipp

Testing the relationship between income inequality and life expectancy: A simple correction for the aggregation effect when using aggregated data - Mayrhofer, Thomas; Schmitz, Hendrik (Journal of Population Economics)

Broke, ill, and obese: is there an effect of household debt on health? - Keese, Matthias; Schmitz, Hendrik (Review of Income and Wealth)

Regional variation in the utilisation of ambulatory services in Germany - Kopetsch, Thomas; Schmitz, Hendrik (Health Economics)

Forschung und Lehre: Freund oder Feind? - Lück, Sonja (Die Betriebswirtschaft)

Behavioral Mechanisms Towards Badges: The Small-Area Hypothesis - Mutter, Tobias; Kundisch, Dennis

Exploring the Relationship Between Local Market Structure and Digitized Customer Experience - Herrmann, Philipp; Rahman, Mohammad

Enriching iTunes App Store categories via topic modeling - Vakulenko, Svitlana; Müller, Oliver; Brocke, Jan vom (International Conference on Information Systems)
Mobile application development is an emerging lucrative and fast growing market. With the steady growth of the number of apps in the repositories the providers will inevitably face the need to fine-grain the existing hierarchy of categories used to organize the apps. In this paper we present a method to bootstrap the categorization process via topic modeling. We apply Latent Dirichlet Allocation (LDA) to the textual descriptions of iTunes apps in order to identify recurrent topics in the collection. We evaluate and discuss the results obtained from training the model on a set of almost 600,000 English-language app descriptions. Our results demonstrate that automated categorization via LDA-based topic modeling is a promising approach, that can help to structure, analyze and manage the content of app repositories. The topics produced complement the original iTunes categories, concretize and extend them by providing insights into the underlying category content.

A Crook is a Crook … But is He Still a Crook Abroad? On the Effect of Immigration on Destination-Country Corruption - Dimant, Eugen; Krieger, Tim; Redlin, Margarete (German Economic Review)

Oppressive governments, dependence on the USA, and anti-American terrorism - Gries, Thomas; Meierrieks, Daniel; Redlin, Margarete (Oxford Economic Papers)
Keywords: Economics and Econometrics

Playing hard to get: an economic rationale for crowding out of intrinsically motivated behavior - Schnedler, Wendelin; Vanberg, Christoph (European Economic Review)

IFRS 7 Disclosures and Risk Perception of Financial Instruments - Bischof, Jannis; Ebert, Michael (Schmalenbach Business Review)

Does mandatory IFRS adoption facilitate debt financing? - Florou, Annita; Kosi, Urska

Cost of Debt for Private Firms Revisited: Voluntary Audits as a Reflection of Risk - Koren, Jernej; Kosi, Urska; Valentincic, Aljosa

Support, Supervision, Feedback and Lecturers Role in the use of the Classroom Response Systems PINGO - Beutner, Marc; Kundisch, Dennis; Magenheim, J.; Zoyke, A. (Proceedings of the World Conference on E-Learning)

Determinants of corporate participation in the IFRS 4 (insurance contracts) replacement process - Kosi, Urska; Reither, Antonia (Accounting in Europe)
This study examines the determinants of financial firms' lobbying behaviour in the replacement process of International Financial Reporting Standard 4 (IFRS 4) Insurance Contracts. Based on comment letters in response to International Accounting Standards Board's (IASB) Exposure Draft 2010/8, we investigate firms' lobbying decisions and their long-term lobbying intensity. Using an international sample of publicly listed financial firms, we show that insurance companies and financially constrained IFRS firms are more likely to lobby the IASB. We also examine the long-term lobbying activity in the IFRS 4 replacement process during the years 2007–2010. We find that insurance companies and firms with dispersed ownership lobby more. Our results are stronger for IFRS firms compared to US generally accepted accounting principles users. Overall, we document intense lobbying by financial firms and present results that are largely consistent with economic consequences of anticipated accounting changes being the main driver of firms' lobbying behaviour. These results are in line with prior findings for non-financial firms.
Keywords: standard setting; IASB; corporate lobbying; financial firms; IFRS 4

Does Financial Statement Audit Reduce the Cost of Debt of Private Firms? - Koren, Jernej; Kosi, Urska; Valentincic, Aljosa (SSRN Electronic Journal)
This study examines the effect of audit on private firms’ cost of debt. We use a sample of 1,949 small private firms operating in the period 2006-2010 with optional financial statement audit. High quality data allows us to construct a more precise interest rate measure than existing studies employ. After controlling for obvious sources of demand for voluntary audits (ownership complexity, subsidiary status, bank relations), we find a robust central result that voluntary audits increase rather than decrease the cost of debt financing, contrary to several existing studies. This finding indicates that voluntary audits are generally treated as “adopting a label” and penalised by creditors, regardless of the perceived auditor quality as a result of the lemon problem in the audit market. Even Big-4 audits increase the cost of debt, likely as a result due to the lemon problem in the audit market, although the increase is smaller than for non-Big-4 audits. The results are sensitive to the estimation method used (OLS, Heckman’s two-step, PSM) and (sub-)sample selection. We show that disregarding the underlying assumptions of these estimation methods may lead to incorrect inferences. Additional analyses show that audited firms’ reported earnings are less informative about future operating performance than earnings of their unaudited counterparts. Our results also indicate that results are sensitive to cost of debt definition and this might have affected the results reported in the existing literature.

The Influence of Peers and Politics on Economic Outcomes - Empirical and Experimental Evidence in the Fields of Social Norms, Politically Connected Firms, Taxation and Climate Change - Janssen, Elmar

Service transition: A viable option for manufacturing companies with declining financial performance? - Eggert, A.; Münkhoff, Eva; Thiesbrummel, C. (43rd EMAC Annual Conference, Valencia)

Service transition versus service infusion: Different pathways to success for service-oriented manufacturers? - Kanuri, V.; Münkhoff, Eva; Scheer, L. K. (ISBM 2014 Academic Conference, San Francisco, CA)

Salespersons’ solution crafting capability: A knowledge-based perspective - Münkhoff, Eva; Eggert, A.; Terho, H.; Haas, A.; Ulaga, W. (ISBM 2014 Academic Conference, San Francisco, CA)

Selling value in business markets: Why a powerful idea often fails - Eggert, A.; Haas, A.; Terho, H.; Ulaga, W.; Münkhoff, Eva (ISBM 2014 Academic Conference, San Francisco, CA)

Revenue and Profit Implications of Industrial Service Strategies - Eggert, Andreas; Hogreve, Jens; Ulaga, Wolfgang; Münkhoff, Eva (Journal of Service Research)
In many business markets, manufacturers seek service-led growth to secure their existing positions and continue to grow in increasingly competitive environments. Using longitudinal data from 513 German mechanical engineering companies and latent growth curve modeling, this study offers a fine-grained view of the financial performance implications of industrial service strategies. By disentangling the revenue and profit implications of industrial service strategies, findings reveal that such strategies increase both the level and the growth of manufacturing firms’ revenue streams. In contrast, they reduce the level but improve the growth of manufacturers’ profits. Results further suggest that services supporting the clients’ actions (SSC) and services supporting the supplier’s product (SSP) affect performance outcomes in different ways. SSCs directly affect revenue and profit streams. In turn, SSPs display only indirect effects on financial performance mediated through SSCs. A moderator analysis identifies two organizational contingencies that facilitate service business success: Only companies with decentralized decision-making processes and a high share of loyal customers can expect favorable financial results from industrial service strategies. In summary, this research provides significant insights and managerial guidance for turning service strategies into financial successes.
Keywords: Organizational Behavior and Human Resource Management; Sociology and Political Science; Information Systems

Embracing complex causality with the QCA method: An invitation - Schneider, Martin; Eggert, Andreas (Journal of Business Market Management)

Are we on track with sustainability literacy? - Hahn, Rüdiger; Reimsbach, Daniel (Journal of Global Responsibility)
Purpose – In this viewpoint, the authors aim to discuss sustainability issues in university education. Balancing what we call the “Accounting View” and the “Sustainability View”, the authors illuminate the status of value relevance of sustainability information and question the depth of business students' processing of this information. Design/methodology/approach – The discussion was triggered by an experimental study on sustainability disclosure which revealed interesting findings related to the participating students' prior sustainability and accounting coursework. The authors start the viewpoint from these findings and contrast them with existing views on sustainability and accounting (education). Findings – The amount of accounting coursework was positively related to the probability of including sustainability information in future stock value estimates, whereas this applied only marginally to sustainability coursework. However, students with more sophisticated sustainability knowledge seemed to scrutinize the given sustainability information more deeply, while students with “pure” accounting knowledge seemed more willing to simply accept the information. Practical implications – The authors argue for advancements in the curriculum for business students that foster critical thinking and might prevent students (and thus potential future managers) from using sustainability information superficially. The authors caution against regarding sustainability issues as an “add-on” to existing courses and curricula and call for a combination of integrating sustainability issues in (core) business courses and offering standalone courses on sustainability management or CSR. Originality/value – Triggered by findings from an experimental study, the authors contrast different opinions on sustainability education of business students and offer a new viewpoint on the (supposed) value relevance of sustainability information for future business leaders.
Keywords: Business and International Management

Modeling sequential R&D investments: a binomial compound option approach - Hauschild, Bastian; Reimsbach, Daniel (Business Research)
Abstract In this paper, we propose a binomial approach to modeling sequential R&D investments. More specifically, we present a compound real options approach, simplifying the existing valuation methodology. Based upon the same set of assumptions as prior models, we show that the number of computational steps for valuing any compound option can be reduced to a single step. We demonstrate the applicability of our approach using the real-world example of valuing a new drug application. Overall, our work provides a heuristic framework for fostering the adoption of binomial compound option valuation techniques in R&D management.
Keywords: Business; Management and Accounting (miscellaneous)

Eine Systematisierung komplementärer Zugänge zur Lehrentwicklung am Beispiel des Förderprogramms Lehren - Jenert, Tobias
Das Förderprogramm Lehren, organisiert von der Alfred Toepfer Stiftung F.V.S., kombiniert und erprobt verschiedene Ansätze zur Entwicklung der Lehrqualität an Hochschulen. Der vorgeschlagene Beitrag charakterisiert die unterschiedlichen Zugänge, beschreibt der Potenziale und Grenzen und reflektiert Möglichkeiten, komplementäre Lehrentwicklungs-Ansätze zu kombinieren. Das "Lehren Jahresprogramm" bringt Lehrende, Hochschuldidaktiker/-innen und Leitungspersonen im Rahmen von fünf themenbezogenen Workshops zusammen. Der Austausch im Rahmen der Workshops soll die Teilnehmenden neben der individuellen Kompetenzentwicklung und gegenseitiger Perspektivübernahme dabei unterstützen, Innovationsprojekte an ihren Hochschulen zu entwickeln bzw. zu implementieren. Das Jahresprogramm vertritt damit einen Ansatz, der Lehrqualität durch die Gestaltung organisationaler Rahmenbedingungen an den Hochschulen zu entwickeln versucht. Mit der Kombination verschiedener Akteursgruppen sowie durch die zentrale Organisation des Programms soll eine Community von Lehrentwickler/-innen geschaffen werden, die Strategien zur lehrbezogenen Organisationsentwicklung an Hochschulen entwickelt und teilt. Demgegenüber setzt das "Lehren-Kolleg" auf einen fachdidaktischen Zugang zur Lehrentwicklung an Hochschulen. So befassen sich im aktuellen Durchgang Teams aus sieben Hochschulen mit der Gestaltung der Mathematikausbildung in den Ingenieurswissenschaften. Auch hier werden von den teilnehmenden Hochschulvertreter/-innen jeweils Innovationsprojekte bearbeitet, wobei diese stets auf die fachdidaktische Fragestellung des Kollegs ausgerichtet sind. In diesem Ansatz spiegelt sich die starke Bedeutung wissenschaftlicher Disziplinen an Hochschulen wider. Die disziplinäre Zugehörigkeit gilt als stärkstes Element der beruflichen Identität von Hochschullehrenden und schlägt sich dementsprechend in den Kulturen einzelner Studienfächer nieder. Der Beitrag stellt die beiden Zugänge zur Lehrentwicklung - organisations- und fachbezogen - vor dem Hintergrund erster Ergebnisse einer umfangreichen Begleitforschung dar. Dabei geht es nicht darum, die Ansätze konkurrierend darzustellen und sie hinsichtlich ihrer Effektivität zu vergleichen (i.S. der Debatte Fach- versus allgemeine Didaktik). Vielmehr werden die komplementären Potenziale und Schwächen herausgearbeitet, um schliesslich das Konzept eines kombinierten Ansatzes der Lehrentwicklung zu entwerfen, der eine möglichst umfangreiche Dissemination im Rahmen der komplexen Organisationsstrukturen von Hochschulen ermöglichen kann.
Keywords: Lehrentwicklung; educational development

A matter of degree: the continuing training gap for women in Europe - Wozny, Caroline; Schneider, Martin (Socio-Economic Review)

Zielorientiertes Management von Logistikdienstleistungen in Netzwerken kooperierender Unternehmen - Puls, Christoph

Integrierte Lagerstandort- und -kapazitätsplanung als Gegenstand der strategischen Logistk - Ortgiese, Malte

Loyalitätswirkung des geschenkten bevorzugten Kundenstatus – Eine theoretische und empirisch-experimentelle Analyse - Steinhoff, Lena

How Profound Is the Allure of Endowed Status in Hierarchical Loyalty Programs? - Eggert, A.; Garnefeld, I.; Steinhoff, Lena (Customer & Service Systems, Special Issue: Customer Empowerment, 1 (1))

Three Perspectives for Making Loyalty Programs More Effective - Steinhoff, Lena; Palmatier, R. W. (Customer & Service Systems, Special Issue: Customer Empowerment, 1 (1))

Consequences of Customer Engagement: How Customer Engagement Alters the Effects of Habit-, Dependence-, and Relationship-Based Intrinsic Loyalty, Marketing Science Institute (MSI) Working Paper Series. - Henderson, C. M.; Steinhoff, Lena; Palmatier, R. W.

Zur Attraktivität von Advance Tax Rulings (ATRs) und Advance Pricing Agreements (APAs) für Investoren und Steuerbehörden: The Attractiveness of Advance Tax Rulings (ATRs) and Advance Pricing Agreements(APAs) for Investors and Tax Authorities, Synopse zur Dissertation - Kortebusch, Pia

AGnovel and other Graphic novels like Twilight - Schneider, Jennifer

Wissenschafts-Praxis-Kooperation in designbasierter Forschung: Im Spannungsfeld zwischen wissenschaftlicher Gültigkeit und praktischer Relevanz - Brahm, Taiga; Jenert, Tobias (Zeitschrift für Berufs-und Wirtschaftspädagogik-Beihefte (ZBW-B))
Designbasierte Forschung zielt darauf, praktische Problemstellungen zu lösen und gleichzeitig wissenschaftliche Theorien (weiter) zu entwickeln. Dabei durchläuft designbasierte Forschung in der Regel die Phasen der Problemdefinition, der Entwicklung eines didaktischen Designs, der zyklischen Design-Implementation sowie der Evaluation und Reflexion in enger Kooperation von Wissenschaft und Praxis. Inwieweit es mittels designbasierter Forschung gelingen kann, wissenschaftliche Gültigkeit und praktische Relevanz von Forschung gleichermassen zu steigern, wird im Beitrag anhand des Konzepts multipler Signifikanzen erörtert. Dabei wird diskutiert, wie die Gestaltung der Kooperation von Forschenden und Praktikern/-innen dazu beitragen kann, die praktische, statistische, klinische und wirtschaftliche Signifikanz des designbasierten Forschungsprozesses sicherzustellen.
Keywords: Design-based research; design research; validity; significance; Bildungsforschung; designbasierte Forschung; Wissenschafts-Praxis-Kommunikation

Nicht für alle gleich: subjektive Wahrnehmungen des Übergangs Schule-Hochschule - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich (Zeitschrift für Hochschulentwicklung)
Beim Übergang von der Schule in die Hochschule stehen Studienanfänger/innen einer Vielzahl von Herausforderungen gegenüber (z. B. Ankommen am Studienort, Bewältigung der Studienanforderungen). Dabei gibt es - abgesehen von deskriptiven Untersuchungen - kaum gesicherte Forschungsergebnisse darüber, in welchem Umfang individuell unterschiedliche Eingangsvoraussetzungen die wahrgenommene Intensität der Übergangsherausforderungen beeinflussen. Mittels einer Längsschnittstudie wird eine Kohorte von Studienanfängerinnen und -anfängern anhand ihrer Selbstwirksamkeit in Gruppen eingeteilt. Es wird gezeigt, dass diese Gruppen sich auch im Ausmass der erwarteten und erlebten Herausforderungen des ersten Studienjahres signifikant unterscheiden.
Keywords: Studienanfänger/innen; Herausforderungen; Übergang; Selbstwirksamkeit; Angst

Die Verjährung des Anspruchs auf Rückerstattung des Bearbeitungsentgelts - Bartlitz, David (Zeitschrift für Bankrecht und Bankwirtschaft (ZBB))

Zeitenwende: Aufklärungspflicht auch über Innenprovisionen - Bartlitz, David; Hoffmann, Jochen (Zeitschrift für Wirtschaftsrecht (ZIP))

Der philosophisch argumentierende Jurist - Versuch einer philosophischen Deutung der Irrtumskategorien des römischen Kaufrechts - Bartlitz, David (Journal on European History of Law (JEHL))

Sanktionen bei mangelnder Bonitätsprüfung durch den Kreditgeber bei Verbraucherkrediten. Anmerkung zu EuGH, Urt. v. 27.03.2014 - C-565/12 - Bartlitz, David (Neue Juristische Wochenschrift (NJW))

Erläuterungs- und Bonitätsprüfungspflicht im Verbraucherkreditrecht - Bartlitz, David; Hoffmann, Jochen (Wertpapier-Mitteilungen (WM))

Asymmetric Nash bargaining solutions and competitive payoffs - Brangewitz, Sonja; Gamp, Jan-Philip (Economics Letters)

Good Practice Methoden: Klicker Fragen - Kundisch, Dennis

Direkte Rückmeldung erwünscht - Kundisch, Dennis

Unsustainable Sovereign Debt - Is the Euro Crisis only the Tip of the Iceberg? - Gries, Thomas; Bilkic, Natascha; Carerras Painter, Ben (International Economics and Economic Policy)

Global Asymmetries and their Implications for Climate and Industrial Policies, in: Pathways to Industrialization in the Twenty-First Century - New Challenges and Emerging Paradigms - Gries, Thomas (Oxford University Press)

Do banking crises cause terrorism? - Gries, Thomas; Meierrieks, Daniel (Economics Letters)

Causality Between Terrorism and Economic Growth - Gries, Thomas; Meierrieks, DAniel (Journal of Peace Research)

Simulation Aided, Self-Adapting Knowledge Based Control of Material Handling Systems - Klaas, Alexander; Laroque, Christoph; Renken, Hendrik; Dangelmaier, Wilhelm (Proceedings of the 2013 Winter Simulation Conference)

Collective generation of subjective situations / measures for online control in transport and storage systems} - Dangelmaier, Wilhelm; Klaas, Alexander

Simulation in Production and Logistics 2013 - Dangelmaier, Wilhelm; Laroque, Christoph; Klaas, Alexander (Proceedings 15th ASIM Conference Simulation in Production and Logistics)

Improving Flow-Based Modeling of Enterprise Systems and Modeling of Custom Warehouse Systems in d³fact - Renken, Hendrik; Dangelmaier, Wilhelm (Proceedings of the 3rd International Conference on Simulation and Modeling Methodologies, Technologies and Applications)

Evaluation of affinely adjustable robust counterpart for the CLSP - Dangelmaier, Wilhelm; Kaganova, Ekaterina

Proactive Self-Adaptation of a Flexible Simulation Based Control System Using Forecasting - Klaas, Alexander; Streit, Daniel; Schilling, Markus; Dangelmaier, Wilhelm (Proceedings of the 11th IFAC Workshop on Intelligent Manufacturing Systems)

Kaskadierte Simulationen und Visualisierungen für die Analyse mechatronischer Systeme in umfangreichen Transportszenarien - Hassan, Bassem; Klaas, Alexander; Wassmann, Helene; Grafe, Michael

A contribution to the anticipation and regulation of behavior in cognitive mechatronic systems in long-term planning and execution - Hartmann, Philip

Determination of safety requirements {\ "a} nden regarding future delivery reliability in compliance with capital commitment restrictions by means of simulation-based optimization - Pater, Jan-Patrick; Laroque, Christoph; Dangelmaier, Wilhelm; Becker, Roland
n the past, the automotive industry developed logistical concepts that were later adapted and modified by other industries. This article is based on a real scenario from the rail vehicle industry in which the introduction of JIT, kitting and complete deliveries has a negative impact on delivery reliability. In order to counteract this, a process was developed which, taking into account the target conflict of delivery reliability and capital commitment, protects the orders in the supply chain against disruptions by means of safety stocks and thus increases delivery reliability.

Current challenges in process simulation - sketch of a solution approach based on model-driven software development - Dangelmaier, Wilhelm; Laroque, Christoph (Production in Germany - Competitiveness in the 21st Century)

Operative Handlungsempfehlungen für eine kostenorientierte Instandhaltungsplanung - Betz, Stefan (Industrielles Controlling - Planung, Steuerung und Kontrolle von Beschaffung, Produktion und Logistik)

Innovationsrisikomanagement bei unsicheren Cash-Flow-Prognosen - Betz, Stefan (Industrielles Controlling - Planung, Steuerung und Kontrolle von Beschaffung, Produktion und Logistik)

Integration von Instandhaltungskosten in das Innovationsrisikomanagement - Betz, Stefan (Jahrbuch für Controlling und Rechnungswesen)

Entscheidungsunterstützung für szenarium-basierte Risikobewertungen - Kundisch, Dennis; Mutter, Tobias; Wegmann, N. (KoR - Zeitschrift für internationale und kapitalmarktorientierte Rechnungslegung)

Classroom Response Systems - Kundisch, Dennis; Magenheim, Johannes; Beutner, Marc; Herrmann, Philipp; Reinhardt, W.; Zoyke, A. (Informatik-Spektrum)

Industrielles Controlling - Planung, Steuerung und Kontrolle von Beschaffung, Produktion und Logistik

Performance Benchmarking for Designing Interaction Routines --- Managing Trade-offs in Service Co-creation with the Data Envelopment Analysis - Becker, Jörg; Beverungen, Daniel; Breuker, Dominic; Dietrich, Hanns-Alexander; Peter Rauer, Hans (Proceedings of the European Research Conference on Information Systems (ECIS) 2013)

On the Design of IT Artifacts and the Emergence of Business Processes as Organizational Routines - Beverungen, Daniel (Proceedings of the 34th International Conference on Information Systems (ICIS))

Local e-Government Transformation --- An International Comparison - Dillon, S; Deakins, E; Beverungen, Daniel; Kohlborn, T; Hofmann, S; Räckers, M (WEBIST)

Old Blunders in New Media? How Local Governments Communicate with Citizens in Online Social Networks - Hofmann, Sara; Räckers, Michael; Beverungen, Daniel; Becker, Jörg (Proceedings of the 46$^{th}$ Hawaii International Conference on System Sciences (HICSS-46))

Capitalizing on Social Media Analysis --- Insights from an Online Review on Business Models - Malsbender, Andrea; Beverungen, Daniel; Voigt, Matthias; Becker, Jörg (Proceedings of the Americas Conference on Information Systems (AMCIS2013))

Much Ado about Nothing? Tracing the Progress of Innovations Borne on Enterprise Social Network Sites - Malsbender, Andrea; Recker, Jan; Kohlborn, Thomas; Beverungen, Daniel; Tanwer, Satya (Proceedings of the 34th International Conference on Information Systems (ICIS))

Digital Social Signal Processing --- Theoretical Underpinning and Research Agenda - Malsbender, Andrea; Voigt, Matthias; Beverungen, Daniel; Rosemann, Michael (Proceedings of the Pacific Asia Conference on Information Systems (PACIS))

Unravelling (E-)Government Channel Selection: A Quantitative Analysis of Individual Customer Preferences in Germany and Australia - Plattfaut, Ralf; Kohlborn, Thomas; Hofmann, Sara; Beverungen, Daniel; Niehaves, Björn; Räckers, Michael; Becker, Jörg (Proceedings of the 46th Hawaii International Conference on System Sciences)

Guidelines for Reporting Productivity Studies: A Review of the Reproducibility of DEA in the Service Sector - Becker, Jörg; Beverungen, Daniel; Breuker, Dominic; Dietrich, Hanns-Alexander; Peter Rauer, Hans (International Journal of Services and Operations Management)

Bridging the Gap Between Manufacturing and Service Through IT-Based Boundary Objects - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuß, Jens (IEEE Transactions on Engineering Management)

Designing Interaction Routines in Service Networks: A Modularity and Social Construction-Based Approach - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuß, Jens (Scandinavian Journal of Information Systems)

Augmenting Analytical CRM Strategies with Social BI - Beverungen, Daniel; Eggert, Mathias; Voigt, Matthias; Rosemann, Michael (International Journal of Business Intelligence Research (IJBIR))

What Makes Local Governments' Online Communications Successful? Insights from a Multi-Method Analysis of Facebook - Hofmann, Sara; Beverungen, Daniel; Räckers, Michael; Becker, Jörg (Government Information Quarterly)